Experimental analysis of the hydrodynamics, flow pattern and wet agglomeration in rotor-stator vortex separators. Issue 3 (June 2017) - Oyegbile, B.A.; Hoff, M.; Adonadaga, M.; Oyegbile, B.O.
Abstract: The effect of the stator geometry, cavity gap and fluid volume on the turbulent aggregation, hydrodynamics and flow pattern in rotor-stator vortex reactors have been investigated using a digital 2D Particle Image Velocimetry (PIV) and visual observation. The results of the study showed a more uniform distribution of the quantified flow parameters—velocity profile and vorticity map in the continuous reactor when compared to the batch reactor. In addition, a high velocity recirculating jet which creates a diverging flow as the jet hits the reactor wall was observed in the batch reactor creating two distinct vortex structures (core and marginal vortex). Frictional losses across the cavity account for much of the difference between the theoretically computed and measured values of the hydrodynamic parameters. The stream pattern obtained from the PIV analysis unexpectedly shows a fairly good correlation with the flow pattern created from the digital video recordings of the pellet motion during the wet agglomeration experiments.